Analysis of Factors that Influence Profit Quality in Manufacturing Companies - Gun Gunawan Rachman (Atestasi : Jurnal Ilmiah Akuntansi, 2021)
Earnings quality is a crucial metric for evaluating corporate performance and comprehending the long-term financial viability. This research examines several factors' impact on earnings quality by analyzing data from manufacturing businesses listed on the IDX. The key determinants in this study are the extent to which profit is sustained over time, the company's scale, and its liquidity level. The data was extracted from financial reports retrieved from the website www.idx.com. This research falls under the category of quantitative analysis. The purposive sampling method acquired the research sample, which involves selecting models based on preset criteria. Using the purposive sampling strategy, a total of 41 firms were obtained. Data analysis techniques include descriptive statistical tests, panel data model selection tests, f-tests, t-tests, and coefficient of determination tests. The hypothesis testing in this research uses Eviews version 10.0 with panel data. The research shows that leverage has a big effect on the quality of profits, but earnings persistence and business size do not have a big effect on the quality of profits in manufacturing businesses.